Deoxynivalenol impairs proliferation and induces apoptosis in primary murine osteoblasts. Issue 2 (7th February 2018) - Wu, Huihui; Sun, Xiao; Zhang, Zhaoqiang; Zhuang, Dongming; Wang, Yu; Li, Xiaoxia; Yu, Guangfu; Lv, Gang; Wang, Na; Li, Qiaoling; Wang, Charles Howard; Yu, Ailian; et al.
ABSTRACT: The effects of deoxynivalenol in different dose including 100, 200, 500, 1000, and 1500 µg/L on primary cranial osteoblasts from fetal mice were investigated. Fluorescence staining, flow cytometric measurement, 3-(4, 5-dimethylthiazol 2-y1)-3, 5-di-phenyltetrazolium bromide assay, quantitative PCR, and Western blot were used for the test. Mineralization and proliferation of osteoblasts decreased upon 100 µg/L and higher deoxynivalenol treatment and apoptosis of osteoblasts was increased upon 500, 1000, and 1500 µg/L deoxynivalenol treatment. Karyopyknosis, membrane breakage, and a decreased number of calcium nodes were also observed upon 500 µg/L deoxynivalenol treatment. The mRNA and protein levels of B-cell lymphoma-2-associated X protein were upregulated, B-cell lymphoma-2 protein downregulated with increasing concentrations of deoxynivalenol treatment and their ratio increased. Deoxynivalenol induces apoptosis of osteoblasts, suggesting a mechanism by which deoxynivalenol can affect murine skeletal development.